If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12b + -6) + -1(7 + -18b) = 0 Reorder the terms: (-6 + 12b) + -1(7 + -18b) = 0 Remove parenthesis around (-6 + 12b) -6 + 12b + -1(7 + -18b) = 0 -6 + 12b + (7 * -1 + -18b * -1) = 0 -6 + 12b + (-7 + 18b) = 0 Reorder the terms: -6 + -7 + 12b + 18b = 0 Combine like terms: -6 + -7 = -13 -13 + 12b + 18b = 0 Combine like terms: 12b + 18b = 30b -13 + 30b = 0 Solving -13 + 30b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 30b = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 30b = 0 + 13 30b = 0 + 13 Combine like terms: 0 + 13 = 13 30b = 13 Divide each side by '30'. b = 0.4333333333 Simplifying b = 0.4333333333
| (2n^2+4n+3)(2n-3)= | | (-7x)(-1/7) | | 76.9-34.782= | | 8x+3.5=36 | | 6-10=1 | | 16x^2+7x-9=0 | | 3(1+2y)-5=6y-2 | | .468*4.8= | | -14.49-3.9d=3.3(d+3.9) | | 5=3n-n+5 | | 576*.6= | | -2x^2+20x=-82 | | a^2-4a-24+6a= | | 3(1-2y)-5=6y-2 | | 2a-10=44+8a | | -2d+18-4b=60 | | 9x+2+5x+4= | | 4x^2=488 | | (x-30)*.5=100 | | -6(1a-2b)-2(5b-4a)= | | -.25x+6=.5x+3 | | y-35=4.7 | | 7x+7+5x+6= | | 4(x+2)-3x+5=x+5 | | x^2+18x=-32 | | 10x+7+4x+7= | | x^2=-169 | | 6x^2+18x^2= | | -2x+30=7(x+3) | | (2x-1)+2(3x+7)=6x-3 | | 12(1/6-2/3x)-20/3(-3/4) | | 2.458+45+16.29= |